Sunspot equilibria in a production economy: Do rational animal spirits cause overproduction? - KAJII, Atsushi (Institutional Knowledge at Singapore Management University, 2009)
We study a standard two-period economy with one nominal bond and one firm. The firm finances the input with the nominal bond in the first period and its profits are distributed to the shareholders in the second period. We show that in the neighbourhood of each efficient equilibrium, a sunspot equilibrium also exists. It is shown that the equilibrium interest rate is lower than the efficient level and that there is overproduction in the sunspot equilibrium, under some conditions. However, there is no sunspot equilibrium if the profit share of the firm can be traded as well as the bond.